An Observational Comparison of Level of Neutral Buoyancy and Level of Maximum Detrainment in Tropical Deep Convective Clouds. Issue 16 (11th August 2020) - Wang, Dié; Jensen, Michael P.; D'Iorio, Jennifer A.; Jozef, Gina; Giangrande, Scott E.; Johnson, Karen L.; Luo, Zhengzhao Johnny; Starzec, Mariusz; Mullendore, Gretchen L.
Abstract: Tropical deep convective clouds are important drivers of large‐scale atmospheric circulation representing the main vertical transport pathway through the depth of the troposphere for heat, momentum, water, and chemical species. The strength and depth of this transport are impacted by the convective updraft size and intensity that are driven by buoyancy, dynamical forcing, and mixing of environmental air, that is, entrainment. In this study, we identify tropical deep convective systems with well‐defined forward anvils using Atmospheric Radiation Measurement (ARM) ground‐based profiling radars, at three ARM fixed sites in the Tropical Western Pacific (TWP; i.e., Manus, Nauru, and Darwin) and three ARM Mobile Facility deployments in Niamey, Niger; Gan Island, Maldives; and Manacapuru, Brazil. We use the difference between the level of neutral buoyancy (LNB) and the level of maximum detrainment (LMD) as a proxy for the effective bulk convective entrainment ( ε p r o x y ). The LNB, the theoretical height that a parcel raised above the level of free convection would reach with no mixing, is calculated based on preconvection radiosonde measurements using parcel theory. The LMD is the height of the maximum reflectivity observed in forward anvil clouds by profiling radars. Deep convective systems over the TWP show higher LNBs that extend to 16.3 km on average and larger ε p r o x y (median value of LNB minus LMD up to 6.5 km) compared to their continental counterparts in the Amazon and West Africa. Oceanic conditions show larger convective available potential energy (CAPE) coupled with higher moisture at low levels, which favors larger ε p r o x y . In contrast, continental cases initiate and develop, under high convective inhibition, steeper environmental lapse rate, and high wind shear conditions, which show smaller offset between LNB and LMD. Deep convective cases that promote significant cold pools at the surface experience less ε p r o x y . Using a Random Forest regression algorithm, CAPE is associated with the highest feature importance score for predicting convective ε p r o x y, followed by low‐level relative humidity. For continental cases, the low‐level wind shear also indicates higher importance. Key Points: A proxy for the effective bulk entrainment for tropical deep convection is estimated based on ARM radiosonde and radar observations Oceanic deep convection in the tropics suggests enhanced effective bulk entrainment, associated with higher CAPE and more moist conditions For continental events, higher prestorm CAPE, higher RH, and stronger wind shear favor increased effective bulk entrainment